The Integration of Women and Minorities into the Auditing Profession since the Civil Rights Period - Madsen, Paul E. (The Accounting Review, 2013)
ABSTRACT: Following the Civil Rights Movement and the “quiet revolution” in women's work over the years from 1950 to 1970, women and minorities increasingly joined the auditing profession while the profession ramped up efforts to encourage integration. The purpose of this study is to rigorously examine how the integration of auditors has evolved since the civil rights and quiet revolution period. The primary distinctive feature of this study is that it evaluates the auditing profession's integration by comparing it to samples of occupations similar to auditing for the purpose of isolating auditing-specific forces influencing integration. I find that the pay structure in auditing is unusually equal, consistent with “equal pay for equal work.” The results for women, Hispanics, and miscellaneous minorities are consistent with members of these groups responding as one might expect to equal pay in auditing: groups that are poorly paid in other occupations select into auditing at higher rates, and groups that are well paid in other occupations select out of auditing at higher rates. The results for blacks are anomalous in that their pay in auditing has been good relative to many comparable occupations, but they have nevertheless been poorly represented in auditing. There are a number of theories that could potentially explain why blacks may be anomalously underrepresented in auditing. To begin to test them, I perform an exploratory analysis of the representation of women and minorities among college freshmen, college graduates, and young auditors. The results suggest that accounting is a popular degree among black college freshmen and that a relatively high percentage of accounting graduates are black. However, although they are well represented in the pool of potential new auditors, black accounting graduates enter the auditing profession at very low rates relative to other occupations requiring levels of education similar to auditing. The results suggest that black underrepresentation in auditing is not due to a lack of awareness among, or role models for, young blacks. Data Availability: Data used in this study are available in the IPUMS-CPS database, which is compiled and distributed by the Minnesota Population Center at the University of Minnesota; the National Survey of College Graduates, which is available from the National Science Foundation; and the Freshmen Survey of the Higher Education Research Institute, which is available to registered users of its website.